Adherence to Positive Airway Pressure Therapy in U.S. Military Personnel With Sleep Apnea Improves Sleepiness, Sleep Quality, and Depressive Symptoms. (1st April 2015) - Mysliwiec, Vincent; Capaldi, Vincent F.; Gill, Jessica; Baxter, Tristin; O'Reilly, Brian M.; Matsangas, Panagiotis; Roth, Bernard J.
ABSTRACT: Objectives: Obstructive sleep apnea (OSA) is frequently diagnosed in U.S. military personnel. OSA is associated with sleepiness, poor sleep quality, and service-related illnesses of insomnia, depression, post-traumatic stress disorder, and traumatic brain injury. Methods: Observational study of active duty military personnel with OSA and adherence to positive airway pressure (PAP) assessed with smart chip technology. Results: 58 men with mean age 36.2 ± 7.7 years, mean body mass index 31.4 ± 3.7 with mean apnea–hypopnea index (AHI) 19.1 ± 19.0 are reported. 23 (39.7%) participants were adherent to PAP, and 35 (60.3%) were nonadherent. No significant differences in baseline demographics, apnea–hypopnea index, service-related illnesses, or clinical instrument scores. Military personnel adherent to PAP had significantly improved sleepiness ( p = 0.007), sleep quality ( p = 0.013), depressive symptoms ( p = 0.01), energy/fatigue ( p = 0.027), and emotional well-being ( p = 0.024). Participants with moderate–severe OSA were more likely to be in the adherent group when compared with participants diagnosed with mild OSA. Conclusions: Military personnel with OSA have low adherence to PAP. Adherence is associated with improved depressive symptoms, sleepiness, sleep quality, energy/fatigue, emotional well-being, and social functioning. Future research should focus on interventions to improve the management of OSA in military personnel.